A parsimonious model of longevity, fertility, HIV transmission and development - Luca Gori; Piero Manfredi; Mauro Sodini (Global Labor Organization (GLO), 2018)
A central policy issue in the battle against HIV in Sub-Saharan Africa (SSA) is whether and when high-prevalence countries might become fully autonomous in designing and implementing their own intervention policies aimed to control the disease. The aim of this research is twofold. First, it develops a framework for explaining economic development in a general equilibrium growth model with endogenous fertility and endogenous longevity under the threat of a deadly enduring infectious disease, as is the case of HIV/AIDS in SSA. Second, it aims to shed light on the interplay between foreign aid and endogenous domestic public policies in those SSA countries severely afflicted by HIV. In particular, it investigates the macro-economic dynamic feasibility and related effects of an intervention policy where the overall amount of resources devoted to HIV/AIDS is the sum of an exogenous component representing foreign aid and an endogenous public expenditure. Both these policies allow to bring HIV under control, but show quite different responses in terms demo-economic variables, mainly passing through the fertility response to the evolving epidemic conditions.
Keywords: C61; C62; J1; J22; O41; O47; 330; HIV transmission; Economic development; Endogenous fertility; Endogenous longevity